PERANAN GLOBAL ENVIRONMENT FACILITY (GEF) DALAM MEMBANTU MENGATASI PERMASALAHAN LINGKUNGAN DI NEGARA CINA 2010-2014 - Abdul Hafhiz; Faisal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The environment is a basic element in human life. Every human activity often involves the environmental elements in it, particularly in the economic development of a nation. Economic progress often carries serious consequences for the environmental sustainability of a country yangtak rarely impact the surrounding countries. This makes the environmental issues to be one of interest by the reviewer study international relations. The emergence of China as a major economic power in the region makes environmental problems in China's internal increasingly complex which also carries implications for relations with its neighbors. Water pollution caused by increasing industrial activity in China led to increasing water pollution that occurred in the country which then began to pollute the surrounding sea due to the flow of the river contaminated by industrial waste and household waste. In addition, one of the biggest polluters are happening in China is air pollution caused by the waste industry. The Global Environment Facility (GEF) is a multilateral financial institution that serves as a conduit of funds to help developing countries in addressing environmental problems. Since the GEF was established in 1991, China is the recipient country with the highest number. In each phase, the amount of help given to GEF China is increasing, whether sourced directly from GEF and co-financing of funds.Keywords: Global Environment Facility, Environments, Phases, environmental damages, air and water pollution in china.